The Stability of Temporal vs. Monetary Valuations - LEE, Leonard (Institutional Knowledge at Singapore Management University, 2010)
This research examines the relative stability of consumer valuations of two fundamental economic resources—time and money—in product decisions. A series of six experiments demonstrates that, in general, money-based valuations (e.g., air fare) lead to more intransitive choices and less consistent preferences than time-based valuations (e.g., flight time), because compared to time-based valuations, monetary valuations lack emotional tags and are more prone to cognitive noise. However, we show that this effect is reversed when the perceived time variability of the given options is high, which increases the role that the inherent ambiguity of time valuation plays in product choice.